A multiband wearable antenna with defected ground structure - Roopan; Samantaray D.; Bhattacharyya S. (My University, 2025)
This work presents the design of a multi-band wearable monopole patch antenna integrated with a defected ground structure. The designed antenna operates over four distinct frequencies viz., 2.12 GHz, 4.78 GHz, 5.57 GHz and 6.11 GHz with the respective fractional bandwidths of 0.94%, 1.04%, 2.5% and 8.18%. The maximum return loss of 51 dB has been achieved over the band 6.05-6.55 GHz while the maximum realized gain of 10.70 dB has been obtained at 6.15 GHz. The simulation has been carried out using Ansys HFSS which has been validated using CST Microwave Studio. The antenna exhibits endfire radiation pattern in its far-field characteristics. The proposed antenna finds its applications in maritime radar, radio LAN, radiolocation, passive sensor and weather radar applications, satellite communication etc. © 2019 URSI. All rights reserved.